PEMANFAATAN VIRTUAL REALITY TERHADAP MINAT BELAJAR SISWA SD - Ayumi Suci; Lili Kasmini; Anggi Susilawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low learning interest of elementary school students, which is indicated by a lack of attention, interest, involvement, and feelings of enjoyment in learning that still uses conventional media. The problem formulation in this study is how the use of Virtual Reality (VR) in the form of 360° videos on the learning interest of elementary school students. This study aims to describe the use of VR in increasing the learning interest of third-grade students in science learning. The study used a qualitative approach with a descriptive type, with 28 research subjects at SD Negeri 22 Banda Aceh. Data collection techniques were carried out through observation, interviews, and documentation, while data analysis was carried out through data reduction, data presentation, and drawing conclusions with validity tests using triangulation. The results showed that before the use of VR, students' learning interest was at a score of 1-2 with a category of sufficient to less (assessment using a scale of 1 to 4, ranging from "Not Good" to "Very Good"). Meanwhile, after the use of VR, there was an increase in all indicators of learning interest, namely feelings of enjoyment, attention, interest, and involvement to the good category. Students appeared more enthusiastic, focused, and active in participating in learning. Thus, it can be concluded that the use of VR in the form of 360° videos is effective in increasing elementary school students' learning interest. Based on the research results, it is recommended that teachers utilize VR media as an innovative learning alternative and improve their competence in using technology to make learning more engaging and effective